Storyboards and Reading Comprehension of Literary Fiction in English - José Mario Molina Naar (Asociación Colombiana de Profesores de Ingles, 2013)
This article reports on a study developed in order to help a group of six limited- proficient students of English (newcomers) to improve their reading comprehension of English novels by designing storyboards, a type of graphic organizer that condenses both images and scripts. The investigation was carried out in a public school in the state of North Carolina, United States, and lasted eight weeks. The following instruments were implemented in order to measure the impact of this investigation: two pre-tests and two posttests, a teacher's journal, students' portfolios, and the results of a reading benchmark. Data were analyzed using cross tabulation and coding of the data collected. The results revealed that storyboards can have a positive impact on English language learners with limited language proficiency.